Anatomopathological and immunohistochemical findings of natural Brucella abortus infection in buffalo uterin and peri-vaginal lymph nodes (Research, Society and Development, 2021)
The present work aimed to evaluate the macro and microscopic lesions and the distribution of Brucella sp. in the reproductive tract of seropositive female buffaloes to brucellosis. Nineteen genital tracts and eighteen peri-vaginal lymph nodes from previous serum reagent animals to brucella were collected from slaughterhouse, processed and submitted to Fisher's exact test (5%). It was not observed uterine macroscopic lesions from non-pregnant and pregnant until the four month, as well as are infrequent in the peri-vaginal lymph nodes. Microscopical lesions were found as lymphocyte clustering in caruncle in the placentome, necrosis and desquamation of chorionic cells, and in the peri-vaginal lymph nodes may occur oedema, increased neutrophil frequency, lymphocyte depletion, lymphoid hyperplasia, congestion, haemorrhage, and vasculitis. Thus, the IHC displayed great sensitivity to identify the presence of the bacterial antigen in tissues of seropositive animals of this species.